PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KOMPETENSI SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI - B1021161119, Elsa Witika (Jurnal Manajemen Update, 2020)
THE EFFECT OF EDUCATION AND TRAINING TOWARDS COMPETENCE AND ITS IMPACT ON EMPLOYEE PERFORMANCEThis study aims to examine and analyze the effects of competence mediation on the effect of training and education on employee performance in Sambas BKPSDMAD. This type of research is causal with a quantitative approach. The population in this study were all employees of BKPSDMAD Sambas. The sample in this study was 34 respondents using purposive sampling method. The data analysis model used is Path Analysis using SPSS version 18.0.Based on the results of the research the first model shows that education and training have a significant effect on competence. The ability of this variable in explaining its effect on competence is 22.6% while the remaining 77.4% is explained by other factors outside the research model. The second model research results show that education and training and competence have a significant effect on employee performance. The ability of these variables in explaining their effects on employee performance was 49.6% while the remaining 50.4% was explained by other factors outside the research model. Keywords: education and training, competence, employee performanceArmstrong, M. (2006). Performance management: Key strategies and practical guidelines. (3rded.). Kogan Page Hasibuan, S.P, Malayu (2006)  Manajemen Sumber Daya Manusia (Edisi Revisi). Bumi Aksara. Jakarta. Hasibun, S. P, Melayu. (2011). Manajemen: Dasar, Pengertian, dan Masalah Bumi. Aksara. Jakarta. Hutapea, Parulian dan Nurianna Thoha (2008) Kompetensi Plus. Jakarta, PT     Gramedia Pustaka Utama. Mangkunegara, Anwar Prabu. (2010). Evaluasi Kinerja Sumber Daya Manusia.  Jakarta : Refika Aditama. Mathis, Robert L. dan John H. Jackson. (2012). Manajemen Sumber Daya Manusia, Edisi Pertama Salemba Empat, Jakarta Notoatmodjo, Soekidjo. (2003) Pendidikan dan Perilaku Kesehatan. Jakarta:Rineka Cipta.  Pasolong, Harbani. (2014). Teori Administrasi Publik. Alfabeta, Bandung. Peraturan Pemerintah Nomor 101 Tahun (2000) tentang Pendidikan dan Pelatihan Jabatan Pegawai Negeri Sipil.  Peraturan Pemerintah Republik Indonesia no 53 tahun 2010 tentang Kewajiban dan Larangan Pegawai Negeri Sipil  Palan,  R.  (2007)  Competency  Management: Teknis Mengimplementasikan Manajemen SDM Berbasis Kompetensi untuk     Meningkatkan     Daya     Saing Organisasi.PPM. Jakarta Sugiyono. (2015). Metode Penelitian Kuantitatif, Kualitatif dan R & D. Bandung: Alfabeta. Sedarmayanti. (2010). Manajemen Sumber Daya Manusia: Reformasi Birokrasi dan Manajemen .Pegawai Negeri Sipil. Bandung: PT. Refika Aditama.